Caffeic Acid Phenethyl Ester (CAPE) Induces VEGF Expression and Production in Rat Odontoblastic Cells. (21st December 2019) - Kuramoto, Hitomi; Hirao, Kouji; Yumoto, Hiromichi; Hosokawa, Yuki; Nakanishi, Tadashi; Takegawa, Daisuke; Washio, Ayako; Kitamura, Chiaki; Matsuo, Takashi
Abstract : Caffeic acid phenethyl ester (CAPE), the main component of propolis, has various biological activities including anti-inflammatory effect and wound healing promotion. Odontoblasts located in the outermost layer of dental pulp play crucial roles such as production of growth factors and formation of hard tissue termed reparative dentin in host defense against dental caries. In this study, we investigated the effects of CAPE on the upregulation of vascular endothelial growth factor (VEGF) and calcification activities of odontoblasts, leading to development of novel therapy for dental pulp inflammation caused by dental caries. CAPE significantly induced mRNA expression and production of VEGF in rat clonal odontoblast-like KN-3 cells cultured in normal medium or osteogenic induction medium. CAPE treatment enhanced nuclear factor-kappa B (NF- κ B) transcription factor activation, and furthermore, the specific inhibitor of NF- κ B significantly reduced VEGF production. The expression of VEGF receptor- (VEGFR-) 2, not VEGFR-1, was up regulated in KN-3 cells treated with CAPE. In addition, VEGF significantly increased mineralization activity in KN-3 cells. These findings suggest that CAPE might be useful as a novel biological material for the dental pulp conservative therapy.